The financial performance of socially responsible investment - Dong, Luyan (2013)
In this paper, I investigate performance of socially responsible investment (SRI) in the US market, in comparison with conventional investment (CI), in terms of funds, portfolios and indexes. A prominent finding is that expenses charged by SRI funds do not evidently result in underperformance of SRI funds, since they are lower than those of CI funds. More importantly, based on various performance estimates for the whole period (April 2007 –March 2013) and two sub periods (April 2007-March 2010 and April 2010-March 2013), no statistically significant difference in performance between SRI and CI is found. The finding indicates that adoption of socially responsible screens does not inevitably scarify investment performance. However, economically, SRI funds seem to underperform characteristics- matched CI funds, while SRI is likely to outperform CI at the fund portfolio and index levels. It may be weak evidence for assumptions that imposing social criteria reduces diversification efficiency and thereby adversely affects performance, but when a SRI portfolio overcomes the shortage by investing in an enough number of assets, it has a better performance than a matched conventional portfolio. If the assumptions are true, socially responsible investors are encouraged to diversify their portfolios by investing in various SRI funds, rather than only focusing on a single fund. Consequently, socially responsible investors are able to do both well and good simultaneously. Moreover, there is no clear evidence that incorporating social screens into investment decisions contributes to better performance in the economic downturn or financial crisis, as the outperformance of SRI funds for the financial crisis period is attributable to their different investment characteristics. Indeed, compared with matched conventional funds, SRI funds have more exposures to small cap, value oriented and low momentum stocks.